2006
DOI: 10.1007/11941378_9
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of Two Provably Secure Cross-Realm C2C-PAKE Protocols

Abstract: Abstract. Password-Authenticated Key Exchange (PAKE) protocols allow parties to share secret keys in an authentic manner based on an easily memorizable password. Byun et al. first proposed a cross realm client-to-client (C2C) PAKE for clients of different realms (with different trusted servers) to establish a key. Subsequent work includes some attacks and a few other variants either to resist existing attacks or to improve the efficiency. However, all these variants were designed with heuristic security analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…the Corrupt query [14,15], or improperly defining the adversarial game [10] may result in a security proof that fails to capture valid attacks (see [10,14,15,32,33] for more details).…”
Section: Related Workmentioning
confidence: 99%
“…the Corrupt query [14,15], or improperly defining the adversarial game [10] may result in a security proof that fails to capture valid attacks (see [10,14,15,32,33] for more details).…”
Section: Related Workmentioning
confidence: 99%
“…For example, Steiner et al's, Abdalla et al's [3], Byun et al's [4] and Yin et al's [5] protocols cannot resist the password guessing attacks [6] [7]. Lin et al [8] and Ding et al [9] thought that the password guessing attacks have three classes:…”
Section: Introductionmentioning
confidence: 99%
“…Since it is widely used to send secret messages using the session key among parties over an insecure public network, therefore, lots of key exchange protocols have been proposed [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, S. Wang et al subsequently found the protocol due to Byun et al was insecure [22]. Later, two schemes for password-authenticated key establishment in a cross-realm setting were proposed in [24,25] but both of them were still pointed out to be insecure in [26]. To the best of our knowledge, no more work address the problem in the cross-realm setting and achieves provable security.…”
Section: Introductionmentioning
confidence: 99%